Hong Kong protests: A quantitative and bottom-up account of resistance against Chinese social media (sina weibo) censorship - Zhao, Jingyi (MedieKultur: Journal of media and communication research, 2017)
Chinese online censorship, though has been deeply explored by many scholars from a top-down perspective and has mostly concentrated on the macro level, it appears that there are few, if any, existing studies that features a bottom-up perspective and explores the micro-level aspects of online media censorship. To fill this research gap, this article uses the Occupy movement in Hong Kong as a research case to analyze social media users’ resistance under conditions of heavy censorship from a bottom-up perspective. That is, the research questions seek to uncover what novel ways Weibo users use to try and circumvent Weibo censorship. It is confirmed that the microbloggers tend to use embedded pictures and user ID names, instead of using text messages to camouflage the sensitive information to share with other users; that Weibo users tend to create new accounts once their original ones have been closed or monitored.